Hepatitis B Virus Splice-Generated Protein Induces T-Cell Responses in HLA-Transgenic Mice and Hepatitis B Virus-Infected Patients - Mancini-Bourgine, Maryline (American Society for Microbiology, 2007)
Hepatitis B virus splice-generated protein (HBSP), encoded by a spliced hepatitis B virus RNA, was recently identified in liver biopsy specimens from patients with chronic active hepatitis B. We investigated the possible generation of immunogenic peptides by the processing of this protein in vivo. We identified a panel of potential epitopes in HBSP by using predictive computational algorithms for peptide binding to HLA molecules. We used transgenic mice devoid of murine major histocompatibility complex (MHC) class I molecules and positive for human MHC class I molecules to characterize immune responses specific for HBSP. Two HLA-A2-restricted peptides and one immunodominant HLA-B7-restricted epitope were identified following the immunization of mice with DNA vectors encoding HBSP. Most importantly, a set of overlapping peptides covering the HBSP sequence induced significant HBSP-specific T-cell responses in peripheral blood mononuclear cells from patients with chronic hepatitis B. The response was multispecific, as several epitopes were recognized by CD8(+) and CD4(+) human T cells. This study provides the first evidence that this protein generated in vivo from an alternative reading frame of the hepatitis B virus genome activates T-cell responses in hepatitis B virus-infected patients. Given that hepatitis B is an immune response-mediated disease, the detection of T-cell responses directed against HBSP in patients with chronic hepatitis B suggests a potential role for this protein in liver disease progression.